The effect of balcony on thermal performance of high rise office building in tropical climate - Ayokunle, Omoyola Tolulope (2015)
The design of balcony has been incorporated into the design of high-rise residential buildings, but has not been well considered in commercial high-rise buildings such as a high-rise office building except for the bioclimatic high-rise buildings. Balcony, which is referred to as an efficient wind box, functions as a thermal control element in buildings by minimizing heat gain into the interior spaces, thus reducing the amount of energy used for cooling load in buildings. This research aims at investigating the effect of balcony on the thermal performance of the interior spaces of high-rise office building. Balcony with the depth of 1m, 1.5m, 2m, and 2.5m were investigated on the 1st, 15th, 25th and 40th floor level at the north, south, west and east orientation of high-rise office building. Cap Square high-rise office building which is situated in the tropical city of Kuala Lumpur was used as a case model. A computer simulation software (Ecotect) was used for the evaluation of the indoor air temperature of the high-rise office with and without the balcony. The investigation was observed during the office hours from 9am to 6pm on the 22nd of March, 22nd of June, 22nd of September and 22nd of December. The result revealed that, on the 22nd of March and the 22nd of June, the maximum reduction of 1.83°C and 1.75°C (respectively) was recorded on the 1st floor level at the west orientation with the balcony of 2.5m, while on the 22nd of September and the 22nd of December, the maximum reduction of 0.31°C was recorded on the 40th floor level at the west orientation with the balcony of 2.5m when the indoor air temperature of the high-rise office buildings with and without the balcony were compared. This study further revealed that, the balcony with the depth of 2.5m is recommended for the 1st, 15th and 25th floor level on the west, north and east orientation, while the balcony of either 2.0m or 2.5m is recommended for the 40th floor level on the south, west and east orientation of high-rise office building.